Anchoring of a hydrophobic heptapeptide (AFILPTG) on silica facilitates peptide unfolding at the abiotic–biotic interface. Issue 33 (12th August 2021) - Volkov, Victor V.; Heinz, Hendrik; Perry, Carole C.
Abstract : We describe the interaction of a hydrophobic peptide with silica. Fitting of structures identified by simulation and use of natural transition orbitals to interpret CD data show that anchoring involves functional side groups, water and metal ions. Abstract : A hydrophobic heptapeptide, with sequence AFILPTG, as part of a phage capsid protein binds effectively to silica particles carrying negative charge. Here, we explore the silica binding activity of the sequence as a short polypeptide with polar N and C terminals. To describe the structural changes that occur on binding, we fit experimental infrared, Raman and circular dichroism data for a number of structures simulated in the full configuration space of the hepta-peptide using replica exchange molecular dynamics. Quantum chemistry was used to compute normal modes of infrared and Raman spectra and establish a relationship to structures from MD data. To interpret the circular dichroism data, instead of empirical factoring of optical activity into helical/sheet/random components, we exploit natural transition orbital theory and specify the contributions of backbone amide units, side chain functional groups, water, sodium ions and silica to the observed transitions. Computed optical responses suggest a less folded backbone and importance of the N-terminal when close to silica. We further discuss the thermodynamics of the interplay of charged and hydrophobic moieties of the polypeptide on association with the silica surface. The outcomes of this study may assist in the engineering of novel artificial bio-silica heterostructures.